La no adquisición de bien inmueble a partir del fraude inmobiliario. - Castañeda Cruzado, Manuel Stefan (2016)
The following paper addresses in timely manner that the legal system both constitutional and civil does not support the transfer of property to the third party in good faith registration from a real estate fraud but there is a mechanism that protects the legitimate owner from article 70 of the Constitution of the State to the theory of existing business regulated clearly and concisely in the book of contracts, at the same time, when making use of property in harmony with social interest and the common good, this is not compatible with a registration extremism guided by transfer systems which our civil system does not set.